Perceived control over health, communication and patient–physician trust. Issue 12 (December 2015) - Gabay, Gillie
Highlights: Perceived control over health had a unique contribution of 8% to the variance of patient–physician trust. Perceived control over health moderated the relationship between participative communication and trust. Known antecedents of trust were validated in a new cultural context. Trust was higher among seculars. Abstract: Objective: Patient–physician trust is linked to higher medication adherence. To date, the relationship between trust and perceived control over health, a strong driver of patient health behavior, has not been tested. This study tested the contribution of patient perceived control over health to the explained variance in patient–physician trust, beyond the contribution of known antecedent. This study also tested the moderation effect of perceived control over health on the relationship between participative communication and patient–physician trust. Methods: This cross sectional study is based on a representative sample of 820 Israeli respondents with identical healthcare plans. Measures were used in previous studies and hold good psychometric properties. Results: Structural equation modeling supported study hypotheses. Patient perceived control over health uniquely contributed eight percent to the explained variance of trust. When perceived control over health was high and perceived communication was participative, trust was higher. Conclusion: Communication with patients is to focus on the enhancement of patient perceived control over health. Practical implications: Training programs should aim at creating awareness among physicians to the importance of perceived control over health and to their ability to enhance it. Training programs should also facilitate the adoption and implementation of participative communication skills.